Effect of Brown Algae Cystoseira trinodis Methanolic Extract on Renal Tissue - Rouhollah Gazor, Ardalan Pasdaran Lashgari, Shabnam Almasi, Saeed Ghasemi (Tabriz University of Medical Sciences, 2016)
Background: C.trinodisis brown algae of Oman Sea coast is used traditionally as a diuretic in Chabahar, Sistan and Baluchestan province of Iran. But no researches have been conducted on the distractive effects of this alga on the renal tissues until now. Methods: Forty-two adult male mice were divided into 6 groups. Control group received normal saline (E0), group (E1) treated with 5mg/kg methanolic extract (ME) and group (E2) to (E5) received 10, 15, 25 and 50 mg/kg of ME of alga respectively. All animals in 6 groups were treated for 2 weeks (once every other day). Finally, histopathological evaluations were made especially by morphology and photometric method. Results: ME of C.trinodis induced histological damage in kidney. Administration of ME in all experimental groups induced severe glomerular congestion, hyaline cast and severe interstitial inflammatory centers in treated groups. All distractive parameter in test groups increased with increasing dose of extract (p<0.05). Conclusion: Results showed that ME of the C.trinodis has a nephrotoxic effect on the renal tissues.